Perkembangan Uji Geser Langsung Skala Ukuran Besar untuk Material Acak Bendungan di Indonesia - Sahadewa, Andhika (Department of Civil Engineering, Diponegoro University, 2025)
Dams offer various benefits to life. In the last decade, Indonesia built above 50 dams. These dams majorly are built from geomaterial fill, including random materials. Random materials are very economical and have a low environmental bad impact, so their use tends to be maximized. Zones of random material often affect dam stability. Unfortunately, the evaluation of random material shear strength, a crucial parameter for dam stability analysis, is challenging. The large particles in random materials become an obstacle in shear strength tests using regular size apparatus. In Indonesia, there are several large-scale direct shear test facilities in laboratory and field to reliably test random material shear strength. Each laboratory test facility is owned by Technical Implementation Unit for Hydraulics and Water Geotechnics, PT. Indra Karya (Persero), and River Basin Organization for Bengawan Solo. The field test facility, called ILSDS, was devised by the Indonesian Geotechnical Inztitute in cooperation with Institut Teknologi Bandung and Universiti Teknologi Malaysia. This paper introduces these facilities and presents the results of ILSDS tests on random materials in Rukoh Dam, Aceh. The test results showed variability in shear strength as well as a unique behavior in the stress- strain relationship related to the random material content itself, such as large-grain rich or fine-grain rich materials. This large-scale testing is cost-effective, simple, and reliable. It is greatly recommended as a regular practice in a dam construction.